The opioid crisis fuelled by health systems: how will future physicians fare? - Kaggwa, Mark Mohan; Devine, Jeremy; Harms, Sheila (BJPsych International, 2023)
The opioid crisis continues to affect many areas worldwide, raising questions regarding prescribing indications. There is no consensus on negotiating the need for pain relief and the potential for medically prescribed opioidrelated harm/addiction. These issues present an enormous educational challenge to physicians in training, particularly those whose mandate is to understand and respond to varying forms of pain. This article examines the perspectives and educational challenges faced by two psychiatry residents from different parts of the globe during the crisis. Is the educational experience of future psychiatrists sufficient to prepare them for the responsibilities that lie ahead?
Keywords: Opioid crisis; Health systems; Indications